EFFICIENT BUSINESS MODEL AS A BASIS FOR THE GROWTH OF THE INVESTMENT COST OF A PROFESSIONAL SPORTS CLUB - O. V. Litvishko; O. M. Golikova (Вестник университета)
The precarious financial condition of sports clubs, combined with negative cash flows and permanent losses, can be the cause of the further collapse of the entire football industry. This is largely due to the European model of the implementation of sports activities, when in the pursuit of a sports result, the basic principles of building a business and financial efficiency go to the background. The article has been devoted to the search questions of an effective business model for the further development of the professional sports industry, taking into account the modern requirements of a market economy. The arguments, that the financial rules, introduced by Union of European Football Associations, will make football clubs profitable projects attractive to investors, are given in the article.